Pengembangan Buku Ajar IPA Berbasis Potensi Lokal Desa Grenden Untuk Meningkatkan Keterampilan Proses Sains Siswa SMP - Desti Fitridiyanti (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
Science process skills are an important aspect in science learning, but in Indonesia science process skills are still relatively low. Science process skills are still not optimally integrated in learning activities at school. This study aims to determine the validity, practicality, and effectiveness of science textbooks based on the local potential of Grenden Village developed to improve students' science process skills on cell recognition material in class VIII junior high school. This research uses the type of Research and Development research. This research uses the ADDIE development model consisting of Analyze, Design, Develop, Implement, and Evaluate. The subject of this research involved students of class VIII F SMPN 1 Puger as a product trial. The research data used consisted of 2, namely primary data including validation sheets, implementation observation sheets, pre-test and post-test, and student response questionnaires, while secondary data included interviews and documentation. The data analysis method used was quantitative descriptive data analysis including validity test, practicality test, and effectiveness test. The results showed that science textbooks based on the local potential of Grenden Village (1) the percentage of validity was 90%. (2) the percentage of practicality is 88%. (3) the percentage of effectiveness is 88%. The conclusion obtained means that science textbooks based on the local potential of Grenden Village to improve the science process skills of junior high school students are valid, practical, and effective.
Reuploud file repository 6 mei 2026_Firli_Tata :: Finalisasi Repositori File 19 Mei 2026_Kurnadi
Keywords: textbook; local potential; science process skills